Nitrogen Dioxide Concentrations in the Air in Increasing Superoxide Dismutase Enzyme and Malondialdehyde Serum Levels in Bus Terminal Officers - Kahar Kahar; Lilis Sulistyorini; Soedjajadi Keman (Universitas Airlangga, 2021)
Introduction: Free radicals in the air such as NO2 , O3 , PM2,5 induce the production of reactive oxygen species (ROS) in the body and stimulates the production of superoxide dismutase (SOD) enzyme. Imbalanced levels of free radicals and antioxidants will trigger the production of malondialdehyde (MDA). This study aimed to analyze the correlation between NO2 concentrations in the air with SOD and MDA levels in bus terminal officers. Methods: This study was an analytical observational and used a cross-sectional design. The population included terminal operational officers and desk administrative officers in the bus terminal. A number of 12 people was chosen as a sample calculated with averaging formula between case and control. The measurement of NO2 concentrations in the ambient air was performed using the Griess Saltzman method. The ELISA method was utilized to analyze the levels of the SOD enzyme, and the TBARS method was used to analyze the level of MDA serum. A statistical test was conducted using a Mann-Whitney test and Independent-2 Sample T-test. Results and Discussion: The average of NO2 concentrations in the ambient air showed 106.5 µg/Nm3 and in the administration room at 17.8 µg/Nm3 . There was a very significantly higher exposure to NO2 in the air towards the level of SOD enzyme (p < 0.01) and to the level of MDA serum (p < 0.01). Conclusion: The high level of exposure to NO2 in the ambient air will increase SOD enzyme and MDA serum production in the body. It is recommended that the officers consume more fruit and vegetables containing vitamins C and E to fulfill the daily nutritional intake for antioxidants, and for the operational officers, always use a mask